Republic of Moldova : Article IV Consultation and Second Reviews under the Extended Fund Facility and Extended Credit Facility Arrangements-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that growth in Moldova is expected to be about 3 percent in 2018. Inflation is forecast to return to target in 2018, following a pickup in 2017. The banking sector has been stable, the fiscal performance has improved and Moldova's external position has strengthened. The outlook, however, is still subject to substantial risks. The program is broadly on track, but continued reform efforts are needed to accelerate growth and improve living standards. Important progress has been made toward cleansing the financial sector, though with delay, including by strengthening supervisory and regulatory frameworks and increasing management and ownership transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet